Contraceptive use and the intention to become pregnant among women attending the Brazilian Unified Health System - Celia Regina Maganha e Melo; Ana Luiza Vilela Borges; Luciane Simões Duarte; Natália de Castro Nascimento (Universidade de São Paulo, 2020)
Objective: to analyze the use of contraceptive methods and the intention to become pregnant among women attending the Brazilian Unified Health System. Method: a cross-sectional study conducted with 688 women aged 18-49 years old, attending the Family Health Strategy Facilities in the eastern part of the city of São Paulo, Brazil, who were awaiting medical or nursing consultation. Data were obtained through interviews with a structured instrument, allocated in tablets. The analysis was conducted with "strong desire to avoid pregnancy" as the dependent variable. Chi-square and multiple logistic regression were used, calculated in Stata 14.2. Results: 56.5% used some contraceptive method, covariates of the strong desire to avoid pregnancy were marital status (OR=0.49; CI95%=0.33-0.74), parity - two and more children (OR=15.9; IC95%=4.29-59.1); and pregnancy planning - planned (OR=0.69; IC95%=0.73-0.94) and ambivalent (OR=2.94; IC95%=1.30-3.83). There was no statistical difference between the strong desire to avoid pregnancy and the type of contraceptive used. Conclusion: women with a strong desire to avoid pregnancy used basically the same types of contraceptive methods as women in general, which shows that they have not been supported to achieve their reproductive preferences.